Internationalisms: Do They Affect or Enrich the Modern Albanian Language? - Vasili, Evis (European Journal of Multidisciplinary Studies, 2016)
Language is a symbol of cultural, national or state identity. For Albanians, language was and is the most important feature establishing their identity. The first attempts to codify the written Albanian language were distinguished since the second half of the nineteenth century by the Albanian scholars, who led the cultural movement "Albanian National Renaissance", where first of all we can mention Konstandin Kristoforidhi and Sami Frashëri. As an isolated Indo-European language, Albanian language is part of the Balkan linguistic connection. Although the Albanian language has not lost its origin, throughout its history it has proven and suffered interventions and major influences not only from the Indo-European but also from non-Indo-European languages. These influences are more directly reflected in the lexicon as the most fluid system of language. Like any other language, the Albanian language has responded to the demands of social development, changes in the field of production, technology, science, culture and so on by enriching and further developing its vocabulary, inter alia, by borrowing words from other languages. Language lexicon flows are larger than outflows and this explains the fact that the lexicon is expanded from generation to generation with new units. In general, there is a large number of words in Albanian language borrowed from Latin, Slavic languages in the south and Turkish. Most of the borrowed words such as anglicisms, germanisms, greecisms, italicisms etc are introduced in Albanian language in written form and orally, mainly in the last thirty years as a result of direct contact of Albanians with European and transatlantic countries, where they have lived and continue to live as immigrants, asylum seekers or workers. The number of foreign lexemes in Albanian language often differs from region to region and even from one person to another. Motivation of borrowing the words from a linguistic community, who regarding the cultural, technical and economic aspect prevails to the other community, is the desire and need to name new terms, objects and events, which are unknown in the language that takes these words. Borrowing new words for new issues also serves to cover linguistic requirements. However, taking foreign expressions does not necessarily show a sign of weakness; in a typical case there is a language enrichment, because new words are attributed to new things, new knowledge or new spiritual values. There are also cases when a word already exists in Albanian, but it is still replaced with the foreign word. In different circumstances both can be used. From this point of view, a question arises: What attitude should be taken for foreign words? Do foreign words enrich or spoil a language?
Keywords: Internationalisms,affect,enrich